Composition and Antimicrobial Activity of the Essential Oils of Tanacetum balsamita L. subsp balsamita and T. chiliophyllum (Fisch et Mey.) Schultz Bip. var. chiliophyllum (Asteraceae) from Turkey - Bagci, Eyup; Kursat, Murat; Kocak, Alpaslan; Gur, Seher (Taylor & Francis Ltd, 2008)
The chemical composition of the essential oils of dried aerial parts of Tanacetum balsamita subsp. balsamita and T.chiliophyllum var. chiliophyllum were analyzed by GC and GC-MS. Forty five and forty six components were identified representing 81.0 % and 84.4 % of the oils, respectively. Trans-chrysanthenol (22.3 %), chrysanthenyl acetate (19.7 %), linalool oxide (11.5 %), camphor (7.5 %), 1,8-cineole (2.7 %) were-found to be major components in T balsamita subsp. balsamita and camphor (28.5 %), 1,8-cineole (17.1 %), camphene (7.1 %), isobornyl propionate (5.4 %), carveol (4.5 %) and borneol (3.5 %) were also found as major constituents in T chiliophyllum var. chiliophyllum. In vitro antimicrobial activities of these oils and two antibiotics against Gram-positive and Gram-negative bacteria and two yeasts were also investigated. The results exhibited that the total oils and antibiotics possess moderate activities against all the tested microorganisms.
Keywords: Tanacetum balsamita subsp balsamita; Tanacetum chiliophyllum var. chiliophyllum; Asteraceae; Essential oil composition; Antimicrobial activity